Viperin is induced following dengue virus type-2 (DENV-2) infection and has anti-viral actions requiring the C-terminal end of viperin. - Karla J Helbig; Jillian M Carr; Julie K Calvert; Satiya Wati; Jennifer N Clarke; Nicholas S Eyre; Sumudu K Narayana; Guillaume N Fiches; Erin M McCartney; Michael R Beard (Public Library of Science (PLoS), 2013)
The host protein viperin is an interferon stimulated gene (ISG) that is up-regulated during a number of viral infections. In this study we have shown that dengue virus type-2 (DENV-2) infection significantly induced viperin, co-incident with production of viral RNA and via a mechanism requiring retinoic acid-inducible gene I (RIG-I). Viperin did not inhibit DENV-2 entry but DENV-2 RNA and infectious virus release was inhibited in viperin expressing cells. Conversely, DENV-2 replicated to higher tires earlier in viperin shRNA expressing cells. The anti-DENV effect of viperin was mediated by residues within the C-terminal 17 amino acids of viperin and did not require the N-terminal residues, including the helix domain, leucine zipper and S-adenosylmethionine (SAM) motifs known to be involved in viperin intracellular membrane association. Viperin showed co-localisation with lipid droplet markers, and was co-localised and interacted with DENV-2 capsid (CA), NS3 and viral RNA. The ability of viperin to interact with DENV-2 NS3 was associated with its anti-viral activity, while co-localisation of viperin with lipid droplets was not. Thus, DENV-2 infection induces viperin which has anti-viral properties residing in the C-terminal region of the protein that act to restrict early DENV-2 RNA production/accumulation, potentially via interaction of viperin with DENV-2 NS3 and replication complexes. These anti-DENV-2 actions of viperin show both contrasts and similarities with other described anti-viral mechanisms of viperin action and highlight the diverse nature of this unique anti-viral host protein.